Interlayer‐Expanded Vanadium Oxychloride as an Electrode Material for Magnesium‐Based Batteries. Issue 3 (6th February 2017) - Minella, Christian Bonatto; Gao, Ping; Zhao‐Karger, Zhirong; Mu, Xiaoke; Diemant, Thomas; Pfeifer, Maxim; Chakravadhanula, Venkata S. K.; Behm, R. Juergen; Fichtner, Maximilian
Abstract: Mg‐based batteries, which use the Mg 2+ shuttle, theoretically offer several advantages compared to the Li technology, such as higher theoretical volumetric capacity (3833 mA h cm −3 ) of the Mg‐metal anode, the possibility to be safely handled in air, and dendrite‐free electrodeposition. In this study, vanadium oxychloride was employed as an electrode material in a Mg‐based battery. As the cell delivered just 45 mA h g −1 in the first cycle, we tried to improve the delivered capacity through preliminary cycling of the VOCl electrode with Li. The strategy is based on the ability of VOCl to expand its interlayer spacing upon intercalation of ions or molecules within them. In fact, a VOCl electrode with expanded interlayer spacing should facilitate the intercalation of Mg 2+, thus leading to higher specific capacities. The Li pretreatment was able to promote the specific capacity by a factor of four (170 mA h g −1 ) after the first discharge at 298 K. Over 130 mA h g −1 was retained at 5 mA g −1 after 70 cycles. Structural and electrochemical characterization was carried out by means of galvanostatic charge/discharge tests, cyclic voltammetry, ex situ X‐ray photoelectron spectroscopy, X‐ray diffraction, transmission electron microscopy coupled with energy‐dispersive X‐ray spectroscopy, and electron energy loss spectroscopy. Inductively coupled plasma optical emission spectrometry was used to determine the concentration of lithium in the electrode. Abstract : Expanding waistline : The picture shows the transition from a non‐expanded to an expanded‐interlayer spacing of the VOCl layered material through preliminary treatment with lithium. Although the original non‐expanded‐VOCl shows only negligible Mg intercalation/deintercalation, the lithium pretreatment enhances the specific capacity to 170 mA h g −1 .